Modeling the Effects of Grade Retention in High School - Stijn Baert; Bart Cockx; Matteo Picchio (Center for Economic Studies and ifo Institute (CESifo), 2015)
A dynamic discrete choice model is set up to estimate the effects of grade retention in high school, both in the short- (end-of-year evaluation) and long-run (drop-out and delay). In contrast to regression discontinuity designs, this approach captures treatment heterogeneity and controls for grade-varying unobservable determinants. A method is proposed to deal with initial conditions and with partial observability of the track choices at the start of high school. Forced track downgrading is considered as an alternative remedial measure. In the long-run, grade retention and its alternative have adverse effects on schooling outcomes and, more so, for less able pupils.
Keywords: C33; C35; I21; 330; education; grade retention; track mobility; dynamic discrete choice models; heterogeneous treatment effects